(3ebGdI aj CLRGA GdWHs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd JMQjJ ai CeQ CLRGA GdWH dCf GdbOeGA bO GNJdahG ai bSejJgG aQi HYVge bO bSe UfGYI GdWH cdgG Edi YdGL GdjO hGSJYeGd GdChjI hGdJOHjQ s
(3BNQgG (B:s
(3Cf fLYd eHOC GdbSeI ef GdeGOI GdJi gi Chdi GdehGO Hge YfO Pdc fUfa EdjgG SGFQ CUfGa GdbSeI Ydi GdWQjb hGdJSgjd GdJi PcQfGgG JeJ ebGdI LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdKGdKI YTQs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs